2021
DOI: 10.1186/s12874-021-01260-7
|View full text |Cite
|
Sign up to set email alerts
|

Intention-to-treat analysis may be more conservative than per protocol analysis in antibiotic non-inferiority trials: a systematic review

Abstract: Background In non-inferiority trials, there is a concern that intention-to-treat (ITT) analysis, by including participants who did not receive the planned interventions, may bias towards making the treatment and control arms look similar and lead to mistaken claims of non-inferiority. In contrast, per protocol (PP) analysis is viewed as less likely to make this mistake and therefore preferable in non-inferiority trials. In a systematic review of antibiotic non-inferiority trials, we compared IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Our study enrolled more histologic subtypes (including ALK+ALCL, Enteropathy-associated T-cell lymphoma (EATL), and others); the differences between the study populations in the two studies may be one of the reasons for the contrary results. In addition, the performance of the intention-to-treat approach in this study may have led to more conservative estimates ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study enrolled more histologic subtypes (including ALK+ALCL, Enteropathy-associated T-cell lymphoma (EATL), and others); the differences between the study populations in the two studies may be one of the reasons for the contrary results. In addition, the performance of the intention-to-treat approach in this study may have led to more conservative estimates ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The calculated non-inferiority margin for the relative risk (RR) difference from the assumed number of events was 2.75 (4%+7%)/4% ([expected event rate control group + non-inferiority margin] / expected event rate) [ 24 ]. All endpoint analyses were performed according to the intention-to-treat (ITT) principle [ 25 ]. In addition, a per protocol (PP) analysis was performed for the primary outcome.…”
Section: Methodsmentioning
confidence: 99%
“…It has, for example, been clearly shown that a lack of statistical power is one of the main limitations of current research in neuroscience [ 24 ], but the situation is exactly the same in the field of rehabilitation [ 25 ]. In addition to the small number of subjects included in the studies, intention to treat analysis is not always straightforward in rehabilitation (e.g., loss in follow-up, change of rehabilitation strategies according to the evolution of the patients through the rehabilitation process and its specific needs) [ 26 ]. This point may weaken the power of individual studies and RCTs.…”
Section: Current Situation and Limitations Of The Research And Its Tr...mentioning
confidence: 99%